Identification of new QTL for salt tolerance from rice variety Pokkali. (6th January 2020) - Chen, Tianxiao; Zhu, Yajun; Chen, Kai; Shen, Congcong; Zhao, Xiuqin; Shabala, Sergey; Shabala, Lana; Meinke, Holger; Venkataraman, Gayatri; Chen, Zhong‐Hua; Xu, Jianglong; Zhou, Meixue
Abstract: Salt stress is an ever‐present threat to rice production worldwide. Rice salinity tolerance is complex, both genetically and physiologically. The success and effectiveness in selecting salt‐tolerant rice variety require the identification of QTL for the tolerance and closely linked molecular markers. In the present study, a RIL population consisting of 148 lines, derived from a cross between IR29 (salt‐sensitive) and Pokkali (salt‐tolerant), was used to identify new QTL for salt tolerance and investigate the relationships between salt stress caused injury and the changes in different physiological and morphological traits at the seedling stage. 14, 470 high‐quality SNP markers generated by the Rice 56K SNP array were converted to 1, 467 bin markers for linkage mapping. A high‐density genetic linkage map covering 1, 680.9 cM was constructed, with the physical to genetic distance ratio being 222 Kb/cM. In total, 23 QTL for different salt tolerance indices were identified, including the previously reported Saltol which is currently used in breeding programmes. Three QTL for salt injury score (SIS) were located on chromosomes 1, 4 and 12, all being closely related to the long‐distant Na + transport from roots to shoots. These QTL showed additive effects, thus can be effectively used in breeding programme to pyramid various tolerance genes.